NUMERICAL MODELING OF GLOBULAR CLUSTERS TIDAL DISSOLUTION - Ryabova, M. V.; Sendzikas, F. G.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2013)
Numerical model of dynamical evolution of globular clusters(GCs) is described, with an emphasis of the mass loss rate in tidal interactions with the Galaxy. On a set of models dependence of the tidal destruction on cluster parameter sand initial conditions, such as: the initial cluster mass, its initial position in the Galaxy, the eccentricity of the orbit–are studied. An analytical description of tidal destruction of GCs and simple estimate of their life times is proposed.